Migração de retorno, diferenciais de salários e autosseleção: evidências para o Brasil. - Queiroz, Vivian dos Santos (2010)
This study use data from 1997 and 2007 Brazilian National Household Survey (PNAD) and the endogenous switching model of migration and earnings with self-selection to examine the performance of return migrants to Brazilians states. Based in exploratory analyses of data we observed that Southeast region have balance a negative net migration, while the Northeast region perform with larger number of migrants driven to source. Compared to non-migrant, return migrant is younger, more educated and usually employed in informal sector. Additionally, it was verified that highest returns of education are related with high level of education. The empirical finds, in turn, permitted to observe that return migrant of male gender, with higher education, employed in the public sector or self-employer, resident in urban or metropolitan areas earns more, in terms of hourly wage, than non-migrants. Furthermore, the main attributes related with probability of return migration are male gender, race (white), high education, family conditions (household head and children) and networks (number of migrants in household). The finds also suggest a positive selection for permanents migrants and support for negative selection of the return migrants, i.e., return migrants are low-skilled in the group of migrants and they move to source due the initial migration not have been well succeeded. However, the experience of remigration still increases the mean wage of migrant in the state of origin.